Kirchenrecht und Kulturkampf: historische Legitimation, politische Mitwirkung und wissenschaftliche Begleitung durch die Schule Emil Ludwig Richters - Ruppert, Stefan (Jus ecclesiasticum, 2002)
Based on the theory that the significance of religious milieus for the legal history of the modern 19th century has been underestimated, Stefan Ruppert explores the vehement struggle between church and state in the 19th century. Underlying the central reaction of the state to the Vatican Council was the debate on the absolute priority of the law. The compromise made by the established churches in settling the dispute was made into law in the Weimar Constitution and is still effective today.